Rural tourism recovery between two COVID-19 waves: the case of Portugal. Issue 6 (19th March 2022) - Marques, Carlos Peixeira; Guedes, Alexandre; Bento, Ricardo
ABSTRACT: During the summer of 2020 intra-national mobility restrictions were lifted in most European countries, and domestic tourism partially cushioned the negative impacts of plunging international arrivals. Considering the perceived risk of crowding, low tourist density destinations were expected to benefit from shifts in tourists' preferences. This paper shows that, in the case of Portugal, preference for tourism in rural areas increased substantially and those regions best positioned to offer rural accommodation experienced a stronger and lasting recovery of domestic demand.